Método para la generación conceptual de soluciones en el diseño de una máquina mezcladora de ladrillos de Arcilla con herramientas CAD/CAE (2022)
The artisanal production of solid clay bricks implies low productivity, since in many plants manual systems are used for the clay mixing process, demanding greater preparation time, labor and a lower number of units produced. This common situation is not foreign to the Tito factory located in the municipality of La Plata (Huila). To solve this problem, it is proposed to create a method for the conceptual generation of solutions in the design of a clay brick mixing machine with CAD/CAE tools. The method used includes four phases that go from the identification of the state of the art of the methods for the conceptual solutions, the determinat ion of the client's requirements, the design, the calculation of variables and the elaboration of the method for the basic design. The results indicate that customer needs, Pareto analysis, QFD method, morphological analysis and concept development should be incorporated. It is concluded that from the development of the concept, this allows productivity to be improved from 300 units to 900.